Dose Articulation in Preclinical and Clinical Stroke Recovery: Refining a Discovery Research Pipeline and Presenting a Scoping Review Protocol - Dalton, Emily; Churilov, Leonid; Lannin, Natasha A.; Corbett, Dale; Hayward, Kathryn S. (Frontiers in Neurology, 2019)
Introduction: Despite an increase in the quality of clinical trials in stroke recovery, interventions have failed to markedly impact the trajectory of recovery after stroke. Failure may be due to the lack of consideration for the complexity of dose and its articulation within research trials. Prior to commencing the scoping review, we identified two research gaps to be addressed. Firstly, transparent application of a multidimensional definition of dose to clinical trial phases and secondly, the development of a quality tool to critique the articulation of dose across the pipeline. Building on this, we present the protocol for a scoping review that aims to synthesis what is known about dose articulation in stroke recovery in preclinical and clinical populations, and characterise research designs and statistical approaches used in dose articulation trials, and the associated advantages and disadvantages. Methods: The scoping review will apply Arksey and O’Malley’s methodological framework. Two systematic searches that target preclinical and clinical literature will be run in Medline and Embase, which will be complimented by consultation with field experts and hand searching of included trials and relevant reviews. Search results will be imported into Covidence for transparent management. One reviewer will screen all abstracts and titles. Two reviewers will screen full text and a third reviewer included to resolve discrepancies. A standardised data charting form will be used to extract information and appraise the intervention description, risk of bias, and quality of both preclinical and clinical studies. Results will be summarised in tabular and narrative format to inform the development of recommendations for future research. Ethics approval is not required as data used will be secondary and de-identified. Conclusion: Development of a new quality tool to appraise the quality of both preclinical and clinical dose studies may serve to strengthen collaborative efforts between the fields. The findings from this review will advance the use of a discovery pipeline in stroke recovery research to ultimately inform clinical practice.